Evaluating glyphosate alternative acetyl-CoA carboxylase–inhibiting herbicides and application timings to terminate cereal rye in soybean - Jose H.S. de Sanctis; Amit J. Jhala (Weed Technology, 2025)
Fall-planted cover crops are becoming popular among growers in the Midwest for various reasons, including their ability to suppress weeds. Cereal rye is the cover crop most often planted in Nebraska. Glyphosate availability was limited in 2022, so growers sought information about glyphosate alternatives for terminating cover crops such as cereal rye. The objectives of this study were to evaluate glyphosate alternative acetyl-CoA carboxylase (ACCase)-inhibiting herbicides for terminating cereal rye 15 d before soybean planting (DBSP), at soybean planting day (SPD), and 15 d after soybean planting (DASP) and their effect on weed control, density, biomass, soybean plant stand, and soybean grain yield. Field experiments were conducted from 2018 to 2020 at South Central Ag Lab near Clay Center, Nebraska. Cereal rye biomass collected 15 d after termination was 394, 1,697, and 3,700 kg ha−1 in 2019 and 330, 1,304, and 4,550 kg ha−1 in 2020, respectively, at the 15 DBSP at SPD and 15 DASP termination timings. Clethodim provided 77% control of cereal rye 15 DBSP compared with greater than 94% control with applications of fluazifop-P-butyl, fluazifop-P-butyl/fenoxaprop-P-ethyl, quizalofop-P-ethyl, and glyphosate. Similarly, at the SPD and 15 DASP termination timings, 66% and 31% control of cereal rye, respectively, were recorded after clethodim was used compared with greater than 92% control after other ACCase-inhibitors and glyphosate were used. Palmer amaranth control at the R5 soybean growth stage was 70%, 88%, and 96%, respectively, at 15 DBSP, SPD, and 15 DASP. Soybean yield was reduced to 2,184 kg ha−1 when cereal rye was terminated at 15 DASP compared with 4,566 kg ha−1 when it was terminated at SPD, and 4,460 kg ha−1 at 15 DBSP.